2022
DOI: 10.1136/bmjopen-2021-054778
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of drug-related hospitalisation among patients visiting emergency departments of Addis Ababa city hospitals in Ethiopia: a multicentre prospective observational study

Abstract: ObjectivesThis study aimed to determine the prevalence, categories and predictors of drug-related hospitalisation (DRH) among patients visiting emergency departments of Addis Ababa city hospitals, Ethiopia.DesignA multicentre prospective observational study was conducted through patients’ interview and chart review.SettingsThe study was undertaken in three tertiary care hospitals in Addis Ababa, Ethiopia.ParticipantsA total of 423 patients fulfilling the inclusion criteria were included.Outcome measuresPrevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…In the present study the most common category of DRP that result in MRHA was noncompliance, 41.4% (95% CI = 33.1–50). This result is similar with studies done in Ethiopia, 16 , 18 India, 33 and Saudi-Arabia. 34 In this study most patients discontinued their mediation when they were “feeling well” 35.85%.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study the most common category of DRP that result in MRHA was noncompliance, 41.4% (95% CI = 33.1–50). This result is similar with studies done in Ethiopia, 16 , 18 India, 33 and Saudi-Arabia. 34 In this study most patients discontinued their mediation when they were “feeling well” 35.85%.…”
Section: Discussionsupporting
confidence: 92%
“…The result is consistent with a study done in Ethiopia 18 and Spain. 26 A much higher prevalence was observed in a study done in Ethiopia (57.9%) 16 and Sweden (41.3%). 6 The prevalence in the present study is lower than the study done in Ethiopia stated previously.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Compared to lower-income countries, we have observed a lower prevalence of DRAs related to Antiinfectives for systemic use. Antiinfectives for systemic use were frequently involved in DRAs in Ethiopia ( Angamo et al, 2017 ; Demessie and Berha, 2022 ), South Africa ( Mouton et al, 2016 ), Nigeria ( Adedapo et al, 2021 ), and India ( Geer et al, 2016 ). Antiinfectives for systemic use were also frequently implicated in DRAs in Brazil ( de Paula et al, 2012 ) during the time when the requirement to be prescription only was not met.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, a substantial proportion of DRPs are potentially preventable. [5][6][7][8] A previous study by Chan et al 9 demonstrated that most (94.5%) DRP-related hospital admissions were due to adverse drug reactions. The average mortality rate among hospitalised patients due to DRPs is 2.7%.…”
Section: Introductionmentioning
confidence: 99%